2014
DOI: 10.1177/0734282913517526
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Tests in Early Childhood

Abstract: Cognitive assessment of young children contributes to high-stakes decisions because results are often used to determine eligibility for early intervention and special education. Previous reviews of cognitive measures for young children highlighted concerns regarding adequacy of standardization samples, steep item gradients, and insufficient floors for young children functioning at lower levels. The present report extends previous reviews by including measures recently published or revised, nonverbal cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(32 reference statements)
1
10
1
Order By: Relevance
“…Our results are consistent with previous reviews, which have reported that many standardized instruments do not meet psychometric expectations (Bogue et al, 2014; DeThorne & Schaefer, 2004; Gokiert et al, 2014; Williams et al, 2014; Visser et al, 2012). To our knowledge, no other review has examined usability criteria in comparable detail with this review.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with previous reviews, which have reported that many standardized instruments do not meet psychometric expectations (Bogue et al, 2014; DeThorne & Schaefer, 2004; Gokiert et al, 2014; Williams et al, 2014; Visser et al, 2012). To our knowledge, no other review has examined usability criteria in comparable detail with this review.…”
Section: Discussionsupporting
confidence: 93%
“…Several sources of information were used for review, including vendor websites, technical manuals, and published test reviews in databases, including Mental Measurements Yearbook Tests in Print and compendium texts. Each criterion was graded as good (✓), adequate (±), or not adequate (✗; adapted from Alfonso & Flanagan, 2009; Cancilla-Menasche, 2011; Williams et al, 2014), in concert with established frameworks of evaluation criteria.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The WIPPSI is usually considered to produce higher FSIQ scores than the WISC, which may account for the higher scores among the 3-year olds. Also, cognitive assessment in younger children is more problematic and unstable than in older ones (52). Therefore, longitudinal studies of children with CHD are needed to develop an accurate picture of cognitive development.…”
Section: Discussionmentioning
confidence: 99%